The devil's sea - Cussler, Dirk (A Dirk Pitt novel, 2021)
"Fearless adventurer Dirk Pitt must unravel a historical mystery of epic importance in the latest novel in the beloved New York Times bestselling series created by the "grand master of adventure" Clive Cussler"--